Chronic Exercise Improves Mitochondrial Function and Insulin Sensitivity in Brown Adipose Tissue - de las Heras, Natalia; Klett-Mingo, Mercedes; Ballesteros, Sandra; Martín-Fernández, Beatriz; Escribano, Óscar; Blanco-Rivero, Javier; Balfagón, Gloria; Hribal, Marta L.; Benito, Manuel; Lahera, Vicente; Gómez-Hernández, Almudena (Frontiers in Physiology, 2018)
The aim of the present work was to study the consequences of chronic exercise training on factors involved in the regulation of mitochondrial remodeling and biogenesis, as well as the ability to produce energy and improve insulin sensitivity and glucose uptake in rat brown adipose tissue (BAT). Male Wistar rats were divided into two groups: 1) control group (C; n=10) and 2) exercise-trained rats (ET; n=10) for 8 weeks on a motor treadmill (5 times per week for 50 min). Exercise training reduced body weight, plasma insulin and oxidized LDL concentrations. Protein expression of ATP-independent metalloprotease (OMA1), short optic atrophy 1 (S-OPA1) and dynamin-related protein 1 (DRP1) in BAT increased in trained rats, and long optic atrophy 1 (L-OPA1) and mitofusin 1 (MFN1) expression decreased. BAT expression of nuclear respiratory factor type 1 (NRF1) and mitochondrial transcription factor A (TFAM), the main factors involved in mitochondrial biogenesis, was higher in trained rats compared to controls. Exercise training increased protein expression of sirtuin 1 (SIRT1), peroxisome proliferator-activated receptor γ coactivator 1α (PGC1α) and AMP-activated protein kinase (pAMPK/AMPK ratio) in BAT. In addition, training increased carnitine palmitoyltransferase II (CPT II), mitochondrial F1 ATP synthase α-chain, mitochondrial malate dehydrogenase 2 (mMDH) and uncoupling protein (UCP) 1,2,3 expression in BAT. Moreover, exercise increased insulin receptor ratio (IRA/IRB ratio), IRA-insulin-like growth factor 1 receptor (IGF-1R) hybrids and p42/44 activation, and decreased IGF-1R expression and insulin receptor substrate 1 (p-IRS-1) (S307) indicating higher insulin sensitivity and favoring glucose uptake in BAT in response to chronic exercise training. In summary, the present study indicates that chronic exercise is able to improve the energetic profile of BAT in terms of increased mitochondrial function and insulin sensitivity.